2019
DOI: 10.1039/c9bm00082h
|View full text |Cite
|
Sign up to set email alerts
|

Cicada and catkin inspired dual biomimetic antibacterial structure for the surface modification of implant material

Abstract: Inspired by cicadas and catkins, a delicate dual biomimetic antibacterial concept was proposed to modify implant material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…In our previous studies, we demonstrated that Si periodic pillar arrays with sub-micron motif sizes could significantly inhibit bacterial adhesion, proliferation, and colonization by a spatial confinement size-effect [34,35]. Our findings suggested that nano-pillar array might be the optimal topography design against bacteria, which was coincident with the design of nature for the bactericidal topographies on the surface of cicada wing [[36], [37], [38], [39], [40], [41]], dragonfly wing [38,41,42], and gecko skin [43]. The findings [34] were reported even before the first announcement of the natural bactericidal topography on the surface of cicada wing [36].…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In our previous studies, we demonstrated that Si periodic pillar arrays with sub-micron motif sizes could significantly inhibit bacterial adhesion, proliferation, and colonization by a spatial confinement size-effect [34,35]. Our findings suggested that nano-pillar array might be the optimal topography design against bacteria, which was coincident with the design of nature for the bactericidal topographies on the surface of cicada wing [[36], [37], [38], [39], [40], [41]], dragonfly wing [38,41,42], and gecko skin [43]. The findings [34] were reported even before the first announcement of the natural bactericidal topography on the surface of cicada wing [36].…”
Section: Introductionmentioning
confidence: 63%
“…However, the clinical application of biomimetic nano-pillar array is not satisfactory [41], mainly because its antibacterial ability against Gram-positive strain including Staphylococcus aureus ( S. aureus ) is not good enough [37]. Since S. aureus usually causes implant-associated infections [3,44], the biomimetic nano-pillar array should be equipped with other antibacterial agents to fulfill the bacteriostatic and bactericidal requirements of clinical application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ye et al [113] fabricated a cicada and catkin inspired dual biomimetic structure which could simultaneously possess higher bacterial anti‐adhesive ability, wider antibacterial range, and longer antibacterial durability. First, the burst release of ZnO nanoslices on the sample surface can kill the pathogenic bacteria chemically [113].…”
Section: Synergetic Antibacterial Strategymentioning
confidence: 99%
“…Ye et al [113] fabricated a cicada and catkin inspired dual biomimetic structure which could simultaneously possess higher bacterial anti‐adhesive ability, wider antibacterial range, and longer antibacterial durability. First, the burst release of ZnO nanoslices on the sample surface can kill the pathogenic bacteria chemically [113]. Then, the dual biomimetic structure will be exposed gradually and begin to exert its physical antibacterial property generated by the special nanoscale topography [113].…”
Section: Synergetic Antibacterial Strategymentioning
confidence: 99%